Back Cover: Nanomaterials for cascade promoted catalytic cancer therapy (View 6/2021). Issue 6 (17th December 2021) - Tong, Zongrui; Gao, Yong; Yang, Huang; Wang, Weilin; Mao, Zhengwei
Abstract : Inspired by catalytic chemistry, cascade strategies utilizing nanomaterials with sophisticated design could improve tumor microenvironments, enhance therapeutic effects and ensure specific therapy. In article number 20200133, Zhengwei Mao, Zongrui Tong, and co‐workers have reviewed nanomaterials with catalytic activity for cascade strategies to promote cancer therapy.